Distribution and Reactivity of Gallates Toward Galvinoxyl Radicals in Sds Micellar Solutions - Effect of the Alkyl Chain Length - Lissi-Gervaso, E; Aspee-Lamas, A; Aliaga-Vidal, C; Aliaga-Vidal, C; Abuin-Saccomano, E (2011)
In this work, we have evaluated the reactivity of methyl gallate, propyl gallate, and n-octyl gallate toward galvinoxyl radicals in homogeneous solution (ethanol) and sodium dodecyl sulfate micelles. In ethanol, the rate of galvinoxyl consumption was independent of the gallate s alkyl chain length. On the other hand, reaction rates in micelles were dependent on the length of the gallate alkyl chain. Measurements of the rate of the reaction at different pH show that, even at pH 7.0, the reaction mainly involves the monodeprotonated anionic form of the gallates. Plots of reaction rates as a function of the surfactant concentration allowed us to evaluate the distribution of the gallates (KGH) and an apparent rate constant defined by the product between the intramicellar rate constant of the anion (kG-) and its partition constant (KG-). The values of the increment of the apparent rate constant per methylene group in the alkyl chain strongly suggest that intramicellar rate constant values are independent of the alkyl chain length. This points to a similar intramicellar localization of the phenolate moiety in the three gallates considered.